Review of CCAFS Scaling Activities - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
> 20 project leaders and -cooperators have been interviewed, with representation of all flagships and regions. 13 CGIAR centers and 1 partner (WUR) participated.